2010
DOI: 10.1590/s0102-76382010000200014
|View full text |Cite
|
Sign up to set email alerts
|

Comparação da perviedade entre artéria radial e veia safena em pacientes em pós-operatório de cirurgia de revascularização miocárdica com retorno dos sintomas

Abstract: Comparação da perviedade entre artéria radial e veia safena em pacientes em pós-operatório de cirurgia de revascularização miocárdica com retorno dos sintomasComparison of patency between radial artery and saphenous vein in a coronary artery bypass grafting post operative with return of the symptoms 219HORTMANN, HC ET AL -Comparison of patency between radial artery and saphenous vein in a coronary artery bypass grafting post operative with return of the symptoms Bras Cir Cardiovasc 2010; 25(2): 218-223 Rev

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Contrasting former studies, which evaluate the RA and SV graft patency in symptomatic patients by angiography ( 1 , 2 , 11 - 15 ), this investigation compared the mid-term follow up of the RA and SV patency rate in asymptomatic patients using a noninvasive diagnostic modality-CT coronary angiography. This work discovered that in the asymptomatic patients, the RA conduits had a suitable patency in two to five years.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Contrasting former studies, which evaluate the RA and SV graft patency in symptomatic patients by angiography ( 1 , 2 , 11 - 15 ), this investigation compared the mid-term follow up of the RA and SV patency rate in asymptomatic patients using a noninvasive diagnostic modality-CT coronary angiography. This work discovered that in the asymptomatic patients, the RA conduits had a suitable patency in two to five years.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tranbaugh et al ( 3 ) demonstrated favorable long-term (14 years) survival using the LITA, SV, and an RA conduit for CABG by comparison to using the LITA and SV. In contrast, Hortmann et al ( 2 ) showed that the RA presented worse results than did the SV as a second graft in CABG, particularly in women who were grafted in the right coronary artery. Also, Fukui et al ( 11 ) reported that the one year patency rate of the RA was significantly lower than that of the free right ITA and SV graft.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations